An Proposal of Securing the Data at Application Level using Enhanced Schmidt Samoa in Big Data - Galla, Narayana; Mokkala, Padmavathamma (International Journal of Computer Sciences and Engineering, 2025)
In the Big data world securing the sensitive data become more complex and time consuming process. In the big data sharing of sensitive, it exacerbates the threat of sensitive data falling into the un-authorized. To combat this sensitive data threat, enterprises turn to cryptosystem. In the cryptosystem encryption is the process of encoding sensitive data so that only authorized or privileged parties can decrypt and read the sensitive data applying this methodology in application level we provide complete security on the sensitive data.